FORMULASI BUBUK EFFERVESCENT SARANG SEMUT (Myrmecodia platyrea) YANG DIPERKAYA JAHE, KAYU MANIS, DAN SECANG SEBAGAI MINUMAN FUNGSIONAL - Puspita Sari; Marga Neo Pratama; Jay Jayus (JURNAL AGROTEKNOLOGI, 2015)
As the demand for functional beverage products is increasing, the exploration of potential local herbs containing bioactive compound is important, since some had been reported to have a beneficial health effect. Therefore, this study will develop a functional beverage from anthill effervescent powder with additions of ginger, cinnamon and sappanwood. The aim of this study was to determine the physico-chemical and sensory characteristics of Myrmecodia platyrea effervescent powder drink enriched with ginger, cinnamon, and sappanwood. This functional effervescent powder was developed under different formula of the extract of Myrmecodia platyrea, ginger, cinnamon, and sappanwood. The quality of the powder was characterized by observing the solubility, polyphenol content and it antioxydative. The lowest solubility was detected in the formula of Myrmecodia platyrea, ginger, cinnamon, and sappanwood with the ratio of 50:20:15:15. However, this formula exhibiting the highest polyphenol content and antioxydative activity. Moreover, based on the sensory test, this formula was also found to be the most preferred flavor by the panelist. The radical scavenging activities of this formula was also as the highest (86%), its polyphenol content was 3.0 mg/g powder and its flavonoid content was 9.15 mg/100g powder. Therefore effervescent powder obtained from the ratio of 50:20:15:15 of Myrmecodia platyrea, ginger, cinnamon, and sappanwood is the most potential to be serve as a functional beverage. Keywords: Myrmecodia platyrea, effervescent, functional beverages, polyphenol